READING DIGITAL TEXT AS A NEW LITERACY IN ELT: TEACHERS’ PERCEPTION & PRACTICES - Laeli, Anita Fatimatul; Setiawan, Slamet; Anam, Syafi’ul (ETERNAL (English, Teaching, Learning, and Research Journal), 2020)
Technological developments in the 21st-century impacted teaching and learning English. one of the impacts of this technological development is reading activities and competencies, reading experienced a phase of change from printed text to digital text. The change from Printed text to digital text requires new literacies, such as locating information and synthesizing online information. This study aims to investigate teachers’ perceptions of reading digital texts in ELT. About twenty-three ELT teachers, both in junior and senior high schools around East Java, were involved in this study. An online open questionnaire was distributed to portray ELT teachers’ attitudes, knowledge, and practices in reading digital text. The study reveals that all teachers have a positive attitude toward the practice of reading digital text. However, most teachers have misconceptions about knowledge and practice in implementing reading digital text activities. Surprisingly, all teachers in this study claimed that they never received a particular workshop to read digital text activities for English class. Hopefully, this study’s result could contribute to the ELT curriculum in responding to the need to facilitate the new literacy in (online) reading and teacher professional development to develop teachers’ reading digital text competencies. However, teachers as facilitators in classroom learning activities must recognize new literacy in online reading (especially reading digital text) to help students achieve reading competence in today’s digital-based information era.